2021
DOI: 10.1016/j.jflm.2021.102255
|View full text |Cite
|
Sign up to set email alerts
|

Conducting remote medical asylum evaluations in the United States during COVID-19: Clinicians’ perspectives on acceptability, challenges and opportunities

Abstract: Background Due to the COVID-19 pandemic, medical evaluations for asylum are being performed predominantly remotely. We sought to describe these evaluations and identify barriers. Methodology This study utilized an online survey to assess clinician perspectives and experiences regarding remote asylum evaluations. Results Clinicians reported positive experiences regarding remote interpretation (85%, 51/60), history taking (82.4%, 61/74), rappor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In virtual IP interviews, difficulties are observed in the lack of material resources (inadequate equipment, Internet connection, and suitable places in the survivor's environment to conduct the interviews). Consistent with previous similar studies (Pogue et al, 2021), these difficulties affect the time of the process, involving more sessions than in face-to-face cases. In addition, due to the difficulties that the virtual format generates in the understanding of non-verbal communication, in a few cases problems have been detected in collecting information and establishing the transference bond with the examinee, where specific difficulties might appear in terms of warmth, empathy, and rapport in the process.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In virtual IP interviews, difficulties are observed in the lack of material resources (inadequate equipment, Internet connection, and suitable places in the survivor's environment to conduct the interviews). Consistent with previous similar studies (Pogue et al, 2021), these difficulties affect the time of the process, involving more sessions than in face-to-face cases. In addition, due to the difficulties that the virtual format generates in the understanding of non-verbal communication, in a few cases problems have been detected in collecting information and establishing the transference bond with the examinee, where specific difficulties might appear in terms of warmth, empathy, and rapport in the process.…”
Section: Discussionsupporting
confidence: 89%
“…The Covid-19 pandemic has affected models of care and forensic assessment of asylum seekers, which, after initially stalling, have shifted significantly to remote formats com-patible with the total or partial lockdown. Different studies have reported on these changes either in assessments conducted by telephone (Cohen et al, 2021), by video call (Mishori et al, 2021), or using a combination of both methodologies (Green et al, 2020;Pogue et al, 2021). While these studies have generally supported the use of remote assessments alone (Greenhalgh et al, 2020;Pogue et al, 2021), others have recommended a hybrid approach (Gruber et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the importance of multilingual translation has grown exponentially thanks to the impact of the COVID-19 pandemic [1,2]. Visual Object Detection [3,4] (moreover, Textual Object Detection), as a central topic of video conference-based remote diagnosis and consultancy [5] has intensified the digital transformation in the medical field.…”
Section: Introductionmentioning
confidence: 99%
“…The issue generates a new 'realtime multilingual data processing' market to catalyze the elimination of existing communication barriers of multilingual video conferences. The adoption of Visual Object Detection (VOD) to the healthcare domain will increase the efficacy of remote diagnosis processes [2], reducing the reaction time in remote consultations. Furthermore, optical character recognition (OCR) is becoming more popular [6], since it is considered a central pillar of many advanced technologies, particularly related to real-time object detection.…”
Section: Introductionmentioning
confidence: 99%